2011
DOI: 10.4321/s1130-01082011000800004
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in the elderly: characteristics and short term results

Abstract: Objective: to analyse the characteristics of colorectal cancer in elderly patients and to assess the outcomes of treatment.Materials and methods: the study included 1924 patients diagnosed with colorectal cancer during a 22 year period . We analysed patient clinical and demographic characteristics as well as their treatment and its outcome.Results: there was an increase in emergency surgery with age, increasing from 13% among patients under 80 years of age to 47% in those over 90 years of age (p = 0.0001). On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Table shows the reported mortality in older adults undergoing emergency major abdominal surgery, younger individuals emergency surgery, and older adults undergoing nonemergency surgery. For example, for emergency colonic operations, in‐hospital mortality ranged from 15% of individuals aged 65 and older at a single institution in the United States to 42% of individuals aged 90 and older at another in Spain . Reported 30‐day mortality ranged from 6% of individuals aged 65 to 79 at one Spanish hospital to 48% of nonagenarians in a national colon cancer database in Denmark .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table shows the reported mortality in older adults undergoing emergency major abdominal surgery, younger individuals emergency surgery, and older adults undergoing nonemergency surgery. For example, for emergency colonic operations, in‐hospital mortality ranged from 15% of individuals aged 65 and older at a single institution in the United States to 42% of individuals aged 90 and older at another in Spain . Reported 30‐day mortality ranged from 6% of individuals aged 65 to 79 at one Spanish hospital to 48% of nonagenarians in a national colon cancer database in Denmark .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study found that odds of death were more than three times as high after emergency major digestive tract surgery (OR = 3.4, 95% CI = 1.67–6.99) . Three additional studies did not report ORs for association between emergency surgery and mortality, but instead presented mortality rates of the emergency and elective cohorts . In all cases, the elective cohort had lower mortality (6%, 8%, and 6%) than their emergency counterparts (29%, 22%, and 21%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations